2014
DOI: 10.1039/c3sc53332h
|View full text |Cite
|
Sign up to set email alerts
|

Strain-promoted sydnone bicyclo-[6.1.0]-nonyne cycloaddition

Abstract: We report the strain-promoted sydnone bicyclo-[6.1.0]-nonyne cycloaddition and demonstrate that this bioorthogonal reaction enables site-specific protein labelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 45 publications
0
64
0
2
Order By: Relevance
“…Alternative 1,3-dipoles such as nitrones (McKay et al, 2011; McKay et al, 2010; Ning et al, 2010), nitrile oxides (Sanders et al, 2011; Singh and Heaney, 2011), diazoalkanes (McGrath and Raines, 2012), and syndones (Wallace and Chin, 2014) have also been explored as means for improving the kinetics and biocompatibility of reactions with multiple-bond partners (primarily strained alkynes, Figure 5E). Strain-promoted alkyne-nitrone cycloaddition (SPANC) reactions demonstrate rate constants up to 60 M −1 s −1 (McKay et al, 2012; McKay et al, 2010; Ning et al, 2010), and have been used for N -terminal peptide modification (Ning et al, 2010), direct protein labeling, and pre-targeted labeling of ligand-receptor interactions on cell surfaces (McKay et al, 2011).…”
Section: B Bioorthogonal Conjugation Strategies and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative 1,3-dipoles such as nitrones (McKay et al, 2011; McKay et al, 2010; Ning et al, 2010), nitrile oxides (Sanders et al, 2011; Singh and Heaney, 2011), diazoalkanes (McGrath and Raines, 2012), and syndones (Wallace and Chin, 2014) have also been explored as means for improving the kinetics and biocompatibility of reactions with multiple-bond partners (primarily strained alkynes, Figure 5E). Strain-promoted alkyne-nitrone cycloaddition (SPANC) reactions demonstrate rate constants up to 60 M −1 s −1 (McKay et al, 2012; McKay et al, 2010; Ning et al, 2010), and have been used for N -terminal peptide modification (Ning et al, 2010), direct protein labeling, and pre-targeted labeling of ligand-receptor interactions on cell surfaces (McKay et al, 2011).…”
Section: B Bioorthogonal Conjugation Strategies and Applicationsmentioning
confidence: 99%
“…Additionally, syndones have been used as 1,3-dipoles in Cu I catalyzed cycloadditions with terminal alkynes (Kolodych et al, 2013), and more recently in strain-promoted cycloadditions with bicyclononyne (rate constant = 0.054 M −1 s −1 , comparable with that of azides). This method was applied to the efficient fluorescent tagging of cyclooctyne-modified proteins (Wallace and Chin, 2014). Recently, the rate of this cycloaddition process has been improved 30-fold by using 4-chlorosyndones ( k 2 = 1.6 M −1 s −1 ) (Taran et al, 2014).…”
Section: B Bioorthogonal Conjugation Strategies and Applicationsmentioning
confidence: 99%
“…Similarly, both our laboratory [27] and Sanders et al [47] reported the reaction of cyclooctynes with nitrile oxides (SPANOC) leading to isoxazoles, which is a factor *10 faster than SPAAC and SPANC. Finally, strain-promoted cycloaddition with diazo-compounds is also known [47] as well as reaction of BCN with sydnone [42,61]. Interestingly, in the field of (4 ?…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%
“…[1] Thec opper-catalyzed (CuAAC) and strain-promoted (SPAAC) azide-alkyne cycloaddition reactions are possibly the most commonly used click reactions for in vitro as well as in vivo ligation applications. [7] Thec opper-free version of this reaction was reported by the group of J. W. Chin [8] and by J. M. Murphy and co-workers. [7] Thec opper-free version of this reaction was reported by the group of J. W. Chin [8] and by J. M. Murphy and co-workers.…”
mentioning
confidence: 99%